2022
DOI: 10.1108/jmtm-11-2021-0439
|View full text |Cite
|
Sign up to set email alerts
|

Green practices and sustainability performance: the exploratory links of organizational culture and quality improvement practices

Abstract: PurposeThe purpose of this study is to examine the direct and indirect effects of organizational culture and quality improvement practices on the relationship between green practices and sustainability performances by using the structural equation modeling (SEM) approach.Design/methodology/approachStructured questionnaires were used to collect data from 330 full-time managerial employees in established businesses. The relationships depicted in the proposed conceptual model were tested through six hypotheses. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 70 publications
0
19
2
Order By: Relevance
“…The NRBV, an expansion of the resource-based view (RBV), has been prevalently utilized in sustainability studies to clarify variations in intra-and interorganizational performance (e.g. Yildiz Çankaya and Sezen, 2019;Saruchera and Asante-Darko, 2021;Fok et al, 2022). It is a competitive advantage theory that propounds the development of an organization and its capability to stay ahead is based on its connection with the natural environment.…”
Section: Literature Review 21 Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The NRBV, an expansion of the resource-based view (RBV), has been prevalently utilized in sustainability studies to clarify variations in intra-and interorganizational performance (e.g. Yildiz Çankaya and Sezen, 2019;Saruchera and Asante-Darko, 2021;Fok et al, 2022). It is a competitive advantage theory that propounds the development of an organization and its capability to stay ahead is based on its connection with the natural environment.…”
Section: Literature Review 21 Theoretical Backgroundmentioning
confidence: 99%
“…RL offer organizations more opportunities to balance their social, environmental and economic outcomes (Saruchera and Asante-Darko, 2021). In addition, according to Fok et al (2022), for obtaining these positive outcomes, the organizational culture must value sustainability, deal with advancing operations and supplier improvement and benefit from support from employees and top management. Following the NRBV theory, this study establishes the links between RL capability and the TBL (environmental, social and economic performance) through the adoption of a sustainability culture.…”
Section: Literature Review 21 Theoretical Backgroundmentioning
confidence: 99%
“…This advances internal (Shuaib and He, 2021) and external performances (Golrizgashti et al. , 2022), adding to the long-term viability of the firm (Fok et al. , 2022b).…”
Section: Research Findingsmentioning
confidence: 99%
“…Fok et al. (2022) suggested that shared social and moral capitals enhance firms’ credibility in accessing green finance and investment. From the above discourse, we propose that: Hypotheses 5 .…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…As explained by Gill (2019), building such links also facilitated the achievement of social and moral capital. Fok et al (2022) suggested that shared social and moral capitals enhance firms' credibility in accessing green finance and investment. From the above discourse, we propose that:…”
Section: Green Organizational Legitimacy and Access To Green Financementioning
confidence: 99%